Globalisation and Cultural Diversity: Implications for Senior Citizens in Indonesia - Zaki Rakhmawan; Imam Sukardi; Yusup Rohmadi (2025)
This academic journal investigates the multifaceted impacts of globalisation and cultural diversity on the elderly population in Indonesia, a nation undergoing significant cultural and societal transformations driven by international interconnectedness. As global influences permeate both urban and rural settings, Indonesia's senior citizens confront distinct challenges related to maintaining cultural heritage, combating social isolation, and adapting to contemporary societal norms. The research scrutinises how globalisation shapes the experiences of Indonesian seniors, with a particular emphasis on cultural adaptation strategies, the dynamics of intergenerational relationships, and access to healthcare services. Through a comprehensive review of both qualitative and quantitative data, this paper aims to illuminate the evolving complexities of ageing within a globalised context. It proposes policy recommendations designed to enhance the welfare of older adults in Indonesia amidst these ongoing changes. This inquiry highlights the necessity of understanding these dynamics to formulate effective interventions that support healthy ageing within culturally diverse and rapidly globalising societies.